The Effectivity of Losartan Tablet for Decreasing Fibrotic Tissue Formation in Gastrocnemius Muscle Injury Grade I of Rabbits - Priono, Boby Harul; Rasyid, Hermawan; Ismiarto, Yoyos; Ramdan, Ahmad (Pharmaceutical Sciences and Research, 2019)
Muscle injuries among athletes require a complete recovery to be able to function optimally as before. However, in spite of implementing the management with PRICE (Protection, Rest, Immobilization, Compression and Elevation), during the recovery processes, fibrotic tissue will be formed, which is an unwanted non-functional muscle. Losartan is a blood pressure-lowering drug which has the inhibitory effect of inhibitory effect of TGF-? cytokines (fibrotic tissue regulators). TGF-? is the key to fibrotic formation and differentiation. Losartan has an effect on decreasing the TGF-? production and it may affect the fibrotic tissue. This research is conducted by an experimental comparative method on the rabbit as study objects. Based on Federer formula sampling, twenty samples totally occurred. The random sampling method is adopted for comparing fibrotic tissue in two different groups (control group and losartan group). Losartan is administered orally. There were significant differences in the proportion of fibrotic tissue between the sample groups. The losartan group showed that the level of fibrotic intensity, distribution, and H-score was decreased compared to the control group. Moreover, the result of Mann Whitney statistic test, for determining the H-score for both groups, showed that p is less than 0.05 (p<0.05), which implies that this research is statistically significant. This research proves that giving Losartan tablets brings a significant impact in reducing the formation of muscle fibrosis in muscle injury grade 1 in gastrocnemius rabbits.